High eggplant (Solanum aethiopicum L.) fruit intake for short duration enhances the antioxidant activity and biochemical parameters in rats - Iheagwam, Franklyn Nonso; Chinedu, Shalom Nwodo (Journal of Phytology, 2024)
Solanum aethiopicum is consumed in large quantities by various ethnic groups within Nigeria. This study evaluated the effect of S. aethiopicum fruit ethanol extract (SAFE) short-term intake at high doses on antioxidant and biochemical properties in rats. Thirty-six male Wistar rats were divided into six experimental groups. Two groups served as controls, while others were treated daily with graded doses of SAFE (500, 1000, 1500 and 2000 mg/kg b.w.) for fourteen days. Liver function, lipid profile, oxidative stress biomarkers, and liver pathology were assayed. Oral administration of SAFE significantly (p<0.05) reduced lipid peroxidation while increasing superoxide dismutase activity and glutathione concentration. Biomarkers of lipid profile and liver function were significantly (p<0.05) improved in SAFE-administered groups without altering the liver microarchitecture. The results suggest that short-term administration of S. aethiopicum fruit at high concentrations improves antioxidants and possesses hypocholesterolaemic properties without inducing hepatic alteration associated with its principles.